2018
DOI: 10.1002/jat.3733
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to perfluorononanoic acid impairs spermatogenesis, steroidogenesis and fertility in male mice

Abstract: Perfluoroalkyl acids (PFAAs) are widely used in commercial applications and that they are ubiquitous and persistent in the environment. Perfluorononanoic acid (PFNA), a member of PFAAs, has been detected in human and wildlife. Previous acute exposure studies have shown the adverse effect of PFNA on the testis. The present study was aimed to examine the effect of chronic PFNA exposure, from prepuberty to adulthood, on testicular functions and fertility in Parkes (P) male mice and to investigate the possible mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…Consistent findings were observed following in utero exposure to PFOA [166]. Male reproductive toxicity, including effects on hormone levels and fertility was observed in PFNA treated mice [98] and gestational exposure to GenX and PFHxS resulted in lower testis weight and a weak but significant association with nipple retention in males, respectively [167,168].…”
Section: Modulates Receptor-mediated Effectssupporting
confidence: 66%
See 1 more Smart Citation
“…Consistent findings were observed following in utero exposure to PFOA [166]. Male reproductive toxicity, including effects on hormone levels and fertility was observed in PFNA treated mice [98] and gestational exposure to GenX and PFHxS resulted in lower testis weight and a weak but significant association with nipple retention in males, respectively [167,168].…”
Section: Modulates Receptor-mediated Effectssupporting
confidence: 66%
“…Similarly, in vivo and in vitro studies have demonstrated that PFOS exposure results in oxidative stress, evidenced by the production of ROS, changes in antioxidant enzymes, elevation of lipid peroxidation products and changes in Nrf2 [32,[95][96][97]. Increased lipid peroxidation and antioxidant enzyme activity were also observed in mouse testes following PFNA exposure [98].…”
Section: Induces Oxidative Stressmentioning
confidence: 89%
“…Immediately after sacrificing the animal, one of the epididymis from each animal was dissected out and used for analysis of sperm counting and viability assay. The cauda epididymal sperm count was carried out according to the World Health Organization (1999) laboratory manual.MTT (3-(4, 5dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) assay for viability of sperm was performed following the method published elsewhere (Singh and Singh, 2018). Briefly, after the sperm count, the sperm suspension was immediately diluted to obtain a concentration of 4 × 10 6 spermatozoa/ ml.…”
Section: F Sperm Parameters (Sperm Count and Viability)mentioning
confidence: 99%
“…Humans are exposed to PFAAs through different routes such as food and water contamination, dermal contact, household dust and air inhalation (Su et al, ). Toxicological studies have shown adverse effects of these chemicals on many physiological processes of the body such as hepatic (Wang, Yan, Zhang, Zhang, & Dai, ), immune (Fang, Zhang, Feng, Zhao, & Dai, ), nervous (Fang, Wu, Li, Yuan, & Wang, ), and reproductive and endocrine systems (Foresta, Tescari, & Di Nisio, ; Singh & Singh, ; Singh & Singh, ). Because of these reasons, PFAAs have received much attention, and concern has thus arisen for their potential health risk to humans and wildlife.…”
Section: Introductionmentioning
confidence: 99%